Measurement of |Vcb| and the form-factor slope in B[bar]→Dℓ−ν[bar]ℓ decays in events tagged by a fully reconstructed B meson - Aubert, Bernard; Marks, Jörg; Schenk, Sebastian; Uwer, Ulrich (Physical review letters, 2010)
We present a measurement of the Cabibbo-Kobayashi-Maskawa matrix element |Vcb| and the form-factor slope ρ2 in B[bar]→Dℓ−ν[bar]ℓ decays based on 460×106 BB[bar] events recorded at the Υ(4S) resonance with the BABAR detector. B[bar]→Dℓ−ν[bar]ℓ decays are selected in events in which a hadronic decay of the second B meson is fully reconstructed. We measure B(B−→D0ℓ−ν[bar]ℓ)/B(B−→Xℓ−ν[bar]ℓ)=(0.255±0.009±0.009) and B(B[bar]0→D+ℓ−ν[bar]ℓ)/B(B[bar]0→Xℓ−ν[bar]ℓ)=(0.230±0.011±0.011), along with the differential decay distribution in B[bar]→Dℓ−ν[bar]ℓ decays. We then determine G(1)|Vcb|=(42.3±1.9±1.4)×10−3 and ρ2=1.20±0.09±0.04, where G(1) is the hadronic form factor at the point of zero recoil.
*BABAR Collaboration: B. Aubert, J. Marks, S. Schenk, U. Uwer [und 489 weitere Personen]
Im Titel steht der Buchstabe B sowie der Buchstabe v mit einem Oberstrich
Im Titel ist der Ausdruck "cb" sowie der zweite Buchstabe l tiefgestellt
Im Titel ist das Minuszeichen hochgestellt
Gesehen am 28.11.2022